Analysis of the anatomic eligibility for transcarotid artery revascularization in Chinese patients who underwent carotid endarterectomy and transfemoral carotid artery stenting - Fan, Weijian; Shi, Weihao; Lu, Shuangshuang; Guo, Wencheng; Tong, Jindong; Tan, Jinyun; Yu, Bo (Frontiers in Cardiovascular Medicine, 2023)
Objective: Transcarotid artery Revascularization (TCAR) is thought to be a promising technique and instrument in treating carotid stenosis with favorable outcomes. Since there remain several differences of anatomic characteristics among races, this study was conducted to investigate the anatomic eligibility of TCAR in Chinese patients underwent carotid revascularization. Methods: A retrospective review of carotid stenosis patients from 2019-2021 was conducted. The anatomic eligibility of TCAR was based on the instruction of the ENROUTE Transcarotid Neuroprotection System. The carotid artery characteristics and configuration of the Circle of Willis (CoW) were evaluated via CT angiography. The demographic, clinical characteristics and procedure-related complications were recorded. Logistic regression was used to analyze the independent factors for TCAR eligibility. Results: Of 289 consecutive patients (222 for carotid endarterectomy [CEA] and 67 for transfemoral carotid artery stenting [TF-CAS]) identified, a total of 215 patients (74.4%) met TCAR anatomic eligibility. Specifically, 83.7% had mild common carotid artery (CCA) puncture site plaque, 95.2% had 4-9 mm internal carotid artery diameters, 95.8% had >6 mm CCA diameter, 98.3% had >5 cm clavicle to carotid bifurcation distance. Female sex (OR, 5.967; 95% CI, 2.545-13.987; P<0.001), older age (OR, 1.226; 95% CI, 1.157-1.299; P<0.001) and higher body mass index (OR, 1.462; 95% CI, 1.260-1.697; P<0.001) were prone to be associated with TCAR ineligibility. In addition, 71 patients with TCAR eligibility (33.0%) were found to combine with incomplete CoW. High-risk for CEA was found in 29 patients (17.3%) with TCAR eligibility and high-risk for TF-CAS was noted in 9 patients (19.1%) with TCAR eligibility. Overall, cranial nerve injury (CNI) was found in 22 patients after CEA while 19 of them (11.3%) met TCAR eligibility. Conclusion: A significant proportion of Chinese patients meet anatomic criteria of TCAR, making TCAR a feasible treatment option in China. Anatomic and some demographic factors play key roles in TCAR eligibility. Further analysis indicates potential reduction of procedure-related complications in high-risk carotid stenosis patients under TCAR procedure.